Flood Insurance - Hyun-Jeong Lee (EDIS)
FCS-3302, a 4-page illustrated fact sheet by Hyun-Jeong Lee, explains flood risk profiles, how flood insurance works, and how to file a flood insurance claim. Includes references. Published by the UF Department of Family Youth and Community Sciences, January 2009.